THE IMPORTANCE OF COMPUTER TECHNOLOGY IN LEARNING ENGLISH IN DISTANCE LEARNING FORMAT - Нұрқашева, Фариза (Вестник ЗКУ, 2021)
The distance learning process is the main direction around the world. Currently, the question of the effective organization of distance education and achieving certain results in this directions is very relevant. The article studied the importance of the formation of skills and competence in teaching English in the process of distance learning. The advantages of information-communication tools in language learning are shown. The main components of distance learning are summarized and the properties of computer technologies are considered for efficient teaching. The concept of monitoring and its importance is specified during distance learning and its great importance for high school students in self-esteem. Differentiated lessons and their results on training platforms in the distance learning process. Reviews and features of effective computer programs in language teaching have proved.